Econometric Models for Forecasting Tourism Demand in Iraq Amid Security Stability Variables (2010-2025) - Auday Sabeeh Lazim (Indonesian Journal of Law and Economics Review, 2026)
General Background: Tourism has become an important contributor to economic diversification and regional development, particularly in countries with significant cultural and historical resources. Specific Background: Iraq possesses substantial tourism potential; however, fluctuations in security conditions have historically influenced tourism demand and complicated long-term planning efforts. Knowledge Gap: Previous studies have often examined tourism demand or security conditions separately, while limited research has integrated security stability variables into advanced tourism forecasting models for Iraq. Aims: This study aims to analyze the relationship between security stability and tourism demand in Iraq and to forecast tourist arrivals for the period 2026–2030 using an econometric approach. Results: The findings reveal a strong and statistically significant positive relationship between security stability and tourism demand. The ARIMAX model demonstrated its suitability for forecasting tourism demand and projected a continued increase in tourist arrivals, potentially reaching approximately 11 million visitors by 2030 under conditions of sustained stability. Novelty: The study integrates a quantitative security stability index with an ARIMAX forecasting model to examine tourism demand within the Iraqi context. Implications: The results suggest that maintaining security stability, strengthening tourism infrastructure, and accelerating digital transformation are essential for supporting future tourism growth and effective tourism planning in Iraq. Keywords: Tourism Demand, Security Stability, ARIMAX Model, Tourism Forecasting, Iraq Key Findings Highlights Strong positive association was identified between safety conditions and visitor arrivals. The selected econometric approach produced reliable medium-term projections. Tourist numbers are expected to continue rising under sustained national stability.